2021
DOI: 10.1145/3414472
|View full text |Cite
|
Sign up to set email alerts
|

Designing Deep Reinforcement Learning for Human Parameter Exploration

Abstract: Software tools for generating digital sound often present users with high-dimensional, parametric interfaces, that may not facilitate exploration of diverse sound designs. In this article, we propose to investigate artificial agents using deep reinforcement learning to explore parameter spaces in partnership with users for sound design. We describe a series of user-centred studies to probe the creative benefits of these agents and adapting their design to exploration. Preliminary studies observing users’ explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…A lexicon of 35 verbal descriptors of the salient morphological characteristics of sound (i.e., basic psychoacoustic features, timbre, and temporal descriptions) was validated and conceptualised in a pack of cards as well in a software interface to facilitate the communication between sound designers and non-experts [5]. Co-Explorer is a software tool that exploits reinforcement learning algorithms to enable creative human(s)machine partnerships in the exploration of high-dimensional, parametric sound spaces [34].…”
Section: A Call For Sound-driven Design Cognition Studiesmentioning
confidence: 99%
“…A lexicon of 35 verbal descriptors of the salient morphological characteristics of sound (i.e., basic psychoacoustic features, timbre, and temporal descriptions) was validated and conceptualised in a pack of cards as well in a software interface to facilitate the communication between sound designers and non-experts [5]. Co-Explorer is a software tool that exploits reinforcement learning algorithms to enable creative human(s)machine partnerships in the exploration of high-dimensional, parametric sound spaces [34].…”
Section: A Call For Sound-driven Design Cognition Studiesmentioning
confidence: 99%
“…However, most of these attempts have highlighted the inherent challenges of this approach due to the difficulty of grasping what AI can and cannot do [56]. In my work (first author), I am exploring how the computational learning mechanisms themselves can become interactive in order to foster exploration and human learning, as we recently explored in the specific domain of sound design [50].…”
Section: Scientific and Artistic Drivesmentioning
confidence: 99%
“…In this context, we propose to look at the emergent field of human-centred ML, which applies user-centred and participatory design methods to design interactive machine learning tools [31,76,81], highlighting the qualitative concepts used by non-ML experts users to evaluate ML compared to quantitative concepts used by ML engineers [2]. Interestingly, Yang et al observed how small data approaches of interactive machine learning helped designers who are not ML experts to craft and experiment with ML to build functional systems [92].…”
Section: As Design Materialsmentioning
confidence: 99%
“…Fiebrink et al's Wekinator [31,33] was designed to allow performers and musicians to craft sound interactions through demonstrations and allowed for incrementally act upon ML components as materials constituting the interaction design. Recently, Scurto et al 's Co-Explorer used interactive reinforcement learning to let people perform sound space exploration by communicating positive or negative reward data to an algorithmic agent [76]. Reinforcement learning was here used to craft sounds as well as exploration behaviours produced by the algorithmic agent.…”
Section: As Creative Materialsmentioning
confidence: 99%
See 1 more Smart Citation